The Influence Of Facilities, Accessibility, And Social Factors On The Motivation To Visit Urban Parks In Jakarta - Rianto; Mira Maharani; Deivy Zulyanti Nasution; Elda Nurmalinda (Journal of Business on Hospitality and Tourism, 2025)
The rapid growth of Jakarta, accompanied by high population density and the reduction of green open spaces, has created a growing need for urban parks that serve as spaces for recreation and social interaction. This study aims to analyze the influence of facilitie, , s, accessibility, and social factors on public motivation to visit five representative urban parks in Jakarta. A quantitative approach with an explanatory survey design was employed, involving 500 respondents from five park locations. The data were analyzed using multiple linear regression. The results show that all three independent variables have a significant simultaneous effect on the motivation to visit. These findings highlight that the combination of quality facilities, ease of access, and a supportive social environment is key to enhancing public participation in the optimal and sustainable use of urban parks.